Software product line test list generation based on harmony search algorithm with constraints support - Alsewari, Abdulrahman A.; Kabir, M. Nomani; Kamal Z., Zamli; Alaofi, Khalid S. (The Science and Information (SAI) Organization Limited, 2019)
In software product line (SPL), selecting product's features to be tested is an essential issue to enable the manufactories to release new products earlier than others. Practically, it is impossible to test all the products’ features (i.e. exhaustive testing). Evidence has shown that several SPL strategies have been proposed to generate the test list for testing purpose. Nevertheless, all the existing strategies failed to produce an optimum test list for all cases. Thus, the current study is aimed to develop a new SPL test list generation strategy based on Harmony Search (HS) algorithm, namely SPL-HS. SPL-HS generates a minimum number of test cases that cover all of the features that are required to be tested based on the required interaction degree (t). The results demonstrate that the performance of SPL-HS is able to compete with the existing SPL strategies for generating test list size.